Common pollen and related allergen components in patients with allergic diseases in the Beijing area - Hou, Yi-Bo; Sun, Jin-Lu (Frontiers in Allergy, 2024)
BackgroundPollen is the most common outdoor allergen that causes allergic rhinitis and asthma, which seriously affects patient quality of life and extensive cross-reactivity occurs between pollen allergens.MethodsThe study enrolled 84 patients with respiratory allergies and at least one pollen allergy who visited the clinic. Specific-IgE was detected via immunoblotting in the sera of patients with positive respiratory allergies to pollen. IgE of the components and cross-reactive carbohydrate determinants (CCD) were evaluated using a fluorescence-encoded microsphere assay.ResultsOur results suggest that Artemisia absinthium, Artemisia vulgaris, Humulus scandens, Amaranthus, Parietaria micrantha allergies are most common in the northern region, and that weed pollen remains the major pollen allergen in the northern region. Among the different age groups, the positive rate of Platanus pollen allergens was significantly higher in patients ≤18 years of age than in those aged >18 years (55.56% vs. 9.17%, χ² = 0.55, p < 0.027). Patients with allergic rhinitis and asthma had an increased positive rate for Betula pollen allergen (20.00% vs. 37.93 χ² = 7.87, p = 0.005) and Platanus pollen allergen (27.27% vs. 51.72%, χ² = 11.05, p = 0.0008) than those with allergic rhinitis alone, although the allergen positivity rate did not significantly differ between sexes. In addition, the positivity of sIgE of allergen components did not reveal a correlation with clinical symptoms and anti-CCD IgE positivity was 1.19% (1/84) among all patients.ConclusionThe study found the distribution characteristics of common pollen allergens in Beijing among patients of different ages and genders and with different allergic diseases, as well as the relationship between pollen allergen components and symptoms. The positivity rate of CCD for respiratory allergic diseases in Beijing was not high as well.